Syntheses and anti-inflammatory activity of azamollugin derivatives. Issue 2 (15th January 2016) - Nishino, Hitomi; Nakajima, Yuki; Kakubari, Yoshiaki; Asami, Nakata; Deguchi, Jun; Nugroho, Alfarius Eko; Hirasawa, Yusuke; Kaneda, Toshio; Kawasaki, Yoko; Goda, Yukihiro; Morita, Hiroshi
Graphical abstract: Abstract: Oxomollugin (2 ) is a degradation product of mollugin (1 ) and a potent inhibitor of NO-production including nuclear factor kappa B signals. In our endeavor to develop a potent anti-inflammatory compound, we synthesized several aza-derivatives of oxomollugin (2 ) and evaluated their NO-production inhibitory activity. Azamollugin (3 ) showed a potent inhibitory activity, and its activity (IC50 0.34 μM) was proved to be more potent than that of oxomollugin (2, IC50 1.3 μM).